Temporal Patterns of Motion in Flexion-extension and Pronation-supination in a Rat Model of Posttraumatic Elbow Contracture. Issue 9 (September 2018) - Dunham, Chelsey L.; Castile, Ryan M.; Havlioglu, Necat; Chamberlain, Aaron M.; Lake, Spencer P.
Abstract: Background: The elbow is highly susceptible to contracture, which affects up to 50% of patients who experience elbow trauma. Previously, we developed a rat model to study elbow contracture that exhibited features similar to the human condition, including persistently decreased ROM and increased capsule thickness/adhesions. However, elbow ROM was not quantitatively evaluated over time throughout contracture development and subsequent mobilization of the joint. Questions/purposes: The purposes of this study were (1) to quantify the time-dependent mechanics of contracture, including comparison of contracture after immobilization and free mobilization; and (2) to determine what changes occur in capsule and joint surface morphology that may support the altered joint mechanics. Methods: A total of 96 male Long-Evans rats were randomized into control and injury (unilateral soft tissue injury/immobilization) groups. Flexion-extension and pronation-supination joint mechanics (n = 8/group) were evaluated after 3, 7, 21, or 42 days of immobilization (IM) or after 42 days of IM with either 21 or 42 days of free mobilization (63 or 84 FM, respectively). After measuring joint mechanics, a subset of these limbs (n = 3/group) was prepared for histologic analysis and blinded sections were scored to evaluate capsule and joint surface morphology. Joint mechanics and capsule histology at 42 IM and 84 FM were reported previously but are included to demonstrate the full timeline of elbow contracture. Results: In flexion-extension, injured limb ROM was decreased compared with control (103° ± 11°) by 21 IM (70° ± 13°) (p = 0.001). Despite an increase in injured limb ROM from 42 IM (55° ± 14°) to 63 FM (83° ± 10°) (p < 0.001), injured limb ROM was still decreased compared with control (103° ± 11°) (p = 0.002). Interestingly, ROM recovery plateaued because there was no difference between injured limbs at 63 (83° ± 10°) and 84 FM (73° ± 19°) (p > 0.999). In pronation-supination, increased injured limb ROM occurred until 7 IM (202° ± 32°) compared with control (155° ± 22°) (p = 0.001), representative of joint instability. However, injured limb ROM decreased from 21 (182° ± 25°) to 42 IM (123° ± 47°) (p = 0.001), but was not different compared with control (155° ± 22°) (p = 0.108). Histologic evaluation showed morphologic changes in the anterior capsule (increased adhesions, myofibroblasts, thickness) and nonopposing joint surfaces (surface irregularities with tissue overgrowth, reduced matrix), but these changes did not increase with time. Conclusions: Overall, flexion-extension and pronation-supination exhibited distinct time-dependent patterns during contracture development and joint mobilization. Histologic evaluation showed tissue changes, but did not fully explain the patterns in contracture mechanics. Future work will use this rat model to evaluate the periarticular soft tissues of the elbow to isolate tissue-specific contributions to contracture to ultimately develop strategies for tissue-targeted treatments. Clinical Relevance: A rat model of posttraumatic elbow contracture quantitatively described contracture development/progression and reiterates the need for rehabilitation strategies that consider both flexion-extension and pronation-supination elbow motion.